Teaching approaches in South African dental schools: direct restorative procedures - Lombard, R; du Preez, I C; Oberholzer, T G; Gugushe, T S (SADJ (Houghton), 2009)
Worldwide the use of amalgam has declined and mercury-containing products are banned in several countries. National and international opinions on amalgam were recently discussed in journals. According to surveys, significant time is spent on the teaching of amalgam in American, Canadian, Irish and United Kingdom Dental Schools. To i) investigate the teaching approaches on direct restorative techniques and materials in South African Dental Schools; ii) compare the teaching approaches of the dental schools in South Africa with each other as well as with the American, Canadian, Irish and United Kingdom schools; iii) use the information of this study as baseline data for future studies on teaching approaches. A questionnaire regarding the teaching and training of direct restorations was e-mailed to the heads of Restorative Dentistry departments in four South African Dental Schools in 2007. Significant time is spent on teaching and training of amalgam as a restorative material. Teaching and training on direct restorations are very similar in all South African Dental Schools. Although there is a decline in the use of amalgam worldwide, significant time is spent on teaching of amalgam restorations in South African Dental Schools and this corresponds to the curriculums of American, Canadian, Ireland and United Kingdom Dental Schools.